Multiculturalism and Security - Case Study: Bosnia and Herzegovina - Bećirević, Edina (Kriminalističke teme, 2004)
In international discours Bosnia and Herzegovina is often mentioned as «multicultural society». BiH has been multicultural before the war, and the three constituent «peoples» (or ethnic communities, Bosniaks, Croats and Serbs) had afunctional «modus viviendi». International negotiatiors and local officials ever since the Dayton agreement keep trying to find the secret of the «modus vivendi» recepie again. However, aggression on BiH that caused internal conflicts between ethnic communities as well, showed that multiculturalism BiH had, was highly vulnerable when «security threat» (read: when ethnic communities feel threatend by each other) appears. This interactive lecture would focus on different conceptions of multiculturalism: in developed western democracies, and in countries in transition (South East European Countries). As a. case study and departing point in discussion Bosnia and Hercegovina ivould be used, mainly because it reflects the main differences betweeen the two mentioned conceptions of multiculturalism.